2021
DOI: 10.3390/bs11070096
|View full text |Cite
|
Sign up to set email alerts
|

The Basic Psychological Needs in the Classroom Scale (BPN-CS)

Abstract: Recent experimental and theoretical studies have shown that the assessment of students’ satisfaction of their basic psychological needs (BPN) can be a powerful resource to identify different areas to improve their well-being, engagement, or learning achievement in school contexts. However, currently, the number of validated tools to assess the satisfaction of the BPN is very low, hindering informed decision-making strategies at the educational level. The aim of this study was to develop and validate the Basic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…Quantitative instrument. The Basic Psychological Needs in the Classroom Scale (BPN-CS) (Conesa and Duñabeitia, 2021) was completed before and after the didactic unit. It measures four factors based on 17 items: autonomy, competence, relatedness, and novelty.…”
Section: Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Quantitative instrument. The Basic Psychological Needs in the Classroom Scale (BPN-CS) (Conesa and Duñabeitia, 2021) was completed before and after the didactic unit. It measures four factors based on 17 items: autonomy, competence, relatedness, and novelty.…”
Section: Data Collectionmentioning
confidence: 99%
“…To validate the Spanish version of the questionnaire, Conesa and Duñabeitia (2021) recruited 1344 Spanish primary school students (8-13 years old). In their study, the results of the CFA for the four-factor model indicated an excellent data fit (χ 2 /df = 1.96; RMSEA = 0.03; CFI = 0.99; TLI = 0.99; SRMR = 0.04) while the fit for the general factor was poorer (χ 2 /df = 6.47; RMSEA = 0.06; CFI = 0.95; TLI = 0.94; SRMR = 0.08) (Conesa and Duñabeitia, 2021). In our study, the Cronbach's alpha values obtained were optimal (>0.85) for autonomy, competence, and relatedness.…”
Section: Data Collectionmentioning
confidence: 99%
“…The reliability value in the pre-test for social responsibility was 0.837 and 0.871 for personal responsibility, while in the post-test it was 0.839 and 0.852, respectively. (3) Basic Psychological Needs Scale: The Psychological Need Satisfaction in Exercise Scale (PNSE) designed by Vlachopoulos and Michailidou [52] was used to measure basic psychological needs; this scale has been validated in the Spanish educational context of secondary education [53] and primary education [54]. The PNSE is composed of 12 items divided into 3 dimensions with 4 items each: (1) autonomy, (2) competence and (3) relatedness.…”
Section: Psychosocial Variablesmentioning
confidence: 99%
“…Higher ratings of autonomy support predict improved student well‐being, and this relationship is completely mediated by students' feelings of fulfillment of their basic needs of competency, autonomy, and relatedness (Neufeld & Malin, 2020). According to self‐determination theory, students are more likely to have better educational outcomes when the three basic psychological needs of autonomy, competence, and relatedness, which directly impact a person's motivation (Conesa & Duñabeitia, 2021), are satisfied (Reeve & Cheon, 2021; Ryan & Deci, 2017). With the rapid development of nurse education in Saudi Arabia, nurse educators must therefore help students become autonomous active learners.…”
Section: Introductionmentioning
confidence: 99%